Co-sponsorship, note verbale, and association behaviour at the UNGA: an analysis of the death penalty moratorium resolutions. Issue 1 (2nd January 2022) - Pascoe, Daniel; Bae, Sangmin
ABSTRACT: Between 2007 and 2018, seven resolutions in favour of a universal moratorium on death penalty executions were adopted by the UN General Assembly. This paper provides an analysis of co-sponsorship and the note verbale of dissociation relating to those seven resolutions. Our assumption is that states which plan to vote 'yes' in the plenary will co-sponsor the resolution beforehand. We also presume that states which vote 'no' in the plenary will sign the note verbale invariably circulated several months later, as a further means of condemnation. However, many countries situate themselves in between these two groups of 'genuine' supporters and opponents. The countries in the middle evince inconsistency between their plenary votes and what we term their 'association behaviour' around the plenary, consisting of co-sponsorship (before) and adherence to the note verbale (after). This article analyses these countries to determine the underlying causes for their ambivalent, or even contradictory, positions concerning the moratorium resolutions. The findings complement not only our own previous research on states' idiosyncratic voting in the moratorium resolutions, but also the broader literature that relies heavily on roll-call voting data to study state behaviour, rather than other means of expressing state preferences within multilateral institutions.